Executive Summary: 2017 ERS/ATS standards for single-breath carbon monoxide uptake in the lung. Issue 1 (3rd January 2017) - Graham, Brian L.; Brusasco, Vito; Burgos, Felip; Cooper, Brendan G.; Jensen, Robert; Kendrick, Adrian; MacIntyre, Neil R.; Thompson, Bruce R.; Wanger, Jack
This document summarises an update to the European Respiratory Society (ERS)/American Thoracic Society (ATS) technical standards for single-breath carbon monoxide uptake in the lung that was last updated in 2005. The full standards are also available online ashttps://doi.org/10.1183/13993003.00016-2016 . The major changes in these technical standards relate to D LCO measurement with systems using rapidly responding gas analysers for carbon monoxide and the tracer gas, which are now the most common type of D LCO instrumentation being manufactured. Technical improvements and the increased capability afforded by these new systems permit enhanced measurement of D LCO and the opportunity to include other optional measures of lung function. Summary of updated technical standards for measuring D LCO ( T LCO ) including the use of rapid gas analyser systems http://ow.ly/TQVG305g3Zq